Pengaruh Jump Stop dan One Two Stop Shot terhadap Kemampuan Shooting - Oktavianus, Irfan; Purnomo, Eko; Yudi, Alex Aldha; carsiwan, Carsiwan; putri, vivi novia eka (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
The problem in this study is the low achievement of the basketball team of the Bukittinggi City Lightning Basketball Club. This study aims to see the effect of jump stop shooting and one two stop shooting exercises on the shooting ability of basketball athletes of the Bukittinggi City Lightning Club. This research is a type of experimental research. The population in this study is 14 boys and 10 girls from the Bukittinggi City Halilintar Basketball Club. Sampling was taken using a proportional sampling technique, so the sample taken in this study was 14 male athletes. This research instrument is through a shooting ability test. The statistical data analysis technique used the liliefors normality test and the t-test with a significant level of ɑ=0.05. The results of the analysis showed: (1) There was an effect of jump stop shoot training on the shooting ability of basketball athletes of the Bukittinggi City Lightning Club. (2) There is an effect of one two stop shoot training on the shooting ability of basketball athletes of the Bukittinggi City Lightning Club. (3) There is an effect between jump stop shoot and one two stop shoot exercises on shooting ability. The one-two stop shoot practice has a greater effect than jump stop shoot on the shooting ability of basketball athletes of the Bukittinggi City Lightning Basketball Club